Pengaruh Kemampuan Kerja Dan Manajemen Konflik Terhadap Kinerja Personel Polres Sampang - Ninik Mulyani; Chammariyah Chammariyah; Ikhbal Gunawan (Universitas 45 Surabaya, 2024)
Ikhbal Gunawan, 2023. The Influence of Work Ability and Conflict Management on Personnel Performance of Sampang Police. Wijaya Putra University Postgraduate Program in Surabaya. This type of research uses explanatory research, the research approach uses a quantitative approach. The research sample was 237 personnel. The aims of this study were 1) to examine and analyze the direct significant effect of work ability on the performance of Sampang Police personnel. 2) To test and analyze the significant direct effect of significant conflict management on the performance of Sampang Police personnel. The results showed that: 1) work ability had a significant positive effect on the performance of Sampang Police personnel with an original sample value of 0.481. 2) Conflict management has a significant positive effect on the performance of Sampang Police personnel with an original sample value of 0.219.